Pre-eruptive magmatic processes associated with the historical (218 ± 14 aBP) explosive eruption of Tutupaca volcano (southern Peru) - Manrique Llerena, Nélida (2020)
Magma recharge into a differentiated reservoir is one of the main triggering mechanisms for explosive eruptions. Here we describe the petrology of the eruptive products of the last explosive eruption of Tutupaca volcano (southern Peru) in order to constrain the pre-eruptive physical conditions (P-T-XH2O) of the Tutupaca dacitic reservoir. We demonstrate that prior to the paroxysm, magma in the Tutupaca dacitic reservoir was at low temperature and high viscosity (735 ± 23 °C), with a mineral assemblage of plagioclase, low-Al amphibole, biotite, titanite, and Fe-Ti oxides, located at 8.8 ± 1.6 km depth (233 ± 43 MPa). The phenocrysts of the Tutupaca dacites show frequent disequilibrium textures such as reverse zonation, resorption zones, and overgrowth rims. These disequilibrium textures suggest a heating process induced by the recharge of a hotter magma into the dacitic reservoir. As a result, high-Al amphibole and relatively high-Ca plagioclase phenocryst rims and microlites were formed and record high temperatures from just before the eruption (840 ± 45 °C). Based on these data, we propose that the recent eruption of Tutupaca was triggered by the recharge of a hotter magma into a highly crystallized dacitic magma reservoir. As a result, the resident dacitic magma was reheated and remobilized by a self-mixing process. These magmatic processes induced an enhanced phase of dome growth that provoked destabilization of the NE flank, producing a debris avalanche and its accompanying pyroclastic density currents.